Feminism as Islamophobia: A review of misogyny charges against Islam - Hasan, Md. Mahmudul (Intellectual Discourse, 2012)
One important feature of Islamophobia is to caricaturize Islam as misogynistic and oppressive to women and thus to advance imperialist hegemony. This “gendered Islamophobia” stigmatizes the religion even though, compared to other world religions, its treatment of women is arguably preferable and more enlightened. Historically, one treasonous use of feminism has been to misappropriate it in order to serve colonial interests and support imperialist wars of occupation that repress subjugated people including women and children. This article argues that ignorance about, and prejudice against, Islam contribute to portraying it as a misogynistic creed. Wrong notions of Islam lead many feminists in Muslim societies to denigrate Islamic teachings and borrow Western ideas to advance women’s causes. Lampooning Islam and replicating Western feminist ideas in Muslim lands have served neither women nor feminism. Such feminist tendencies rather give a bad name to the women’s rights movement and fuel controversy, anger and resentment among Muslims.